Citrus Under Protective Screen (CUPS) production systems - Arnold Schumann; Ariel Singerman; Alan L. Wright; Rhuanito S. Ferrarezi (EDIS)
An overview of a new citrus production system targeting HLB-free, premium quality fruit for the fresh market is provided.